POTENTIAL USE OF AN EXTRACELLULAR ENZYME OF a-AMYLASE FROM INDIGENOUS INDONESIAN MESOPHILIC BACTERIA - Puji Lestari; Nur Richana; Rina Masriani (Indonesian Agency for Agricultural Research and Development, 2013)
Amylase enzyme has a great significance for industrial usages in Indonesia. However, this enzyme is still imported. The use of bacteria in biotechnological process of industrial products such as enzyme production has stimulated the exploration of extracellular amylase producing bacteria. This study aimed to identify and analyze the potential use of amylolytic bacterial enzymes for hydrolyzing cassava starch. Two bacterial isolates, i.e. MII-10 and DKW-8 originated from Indonesia soil were identified based on their morphological, physiological and biochemical properties according to the standard protocol. The isolates were then cultivated on fermentation medium and their growth pattern and enzymatic assays were observed. The acetone-precipitated crude enzyme harvested based on predetermined cultivation time was used for enzymatic hydrolysis product characterization on cassava starch using thin layer chromatography (TLC). The results showed that the mesophilicbacteria isolates (MII-10 and DKW-8) were belonged to Bacillus licheniformis. The maximum bacterial cell growth and enzyme activity were reached at 48 hours after incubation. The MII-10 isolate was found more stable than DKW-8 in producing amylase enzyme. Amylase produced by the MII-10 and DKW- 8 isolates was identified to be an endo-a-amylase as confirmed by oligosaccharides and dextrin of the random hydrolysisproducts. Relatively high dextrose equivalence (DE) value of a-amylase of MII-10 (DE of 9.96) suggests that the enzyme is prospective for saccharification of starchy material in glucose syrup industry.